Dual muscle-liver transduction imposes immune tolerance for muscle transgene engraftment despite preexisting immunity - Bartolo, Laurent (JCI Insight, 2019)
Immune responses to therapeutic transgenes are a potential hurdle to treat monogenic muscle disorders. These responses result from the neutralizing activity of transgene-specific B cells and cytotoxic T cells recruited upon gene transfer. We explored here how dual muscle-liver expression of a foreign transgene allows muscle transgene engraftment after adenoassociated viral vector delivery. We found in particular that induction of transgene-specific tolerance is imposed by concurrent muscle and liver targeting, resulting in the absence of CD8(+) T cell responses to the transgene. This tolerance can be temporally decoupled, because transgene engraftment can be achieved in muscle weeks after liver transduction. Importantly, transgene-specific CD8(+) T cell tolerance can be established despite preexisting immunity to the transgene. Whenever preexisting, transgene-specific CD4(+) and CD8(+) memory T cell responses are present, dual muscle-liver transduction turns polyclonal, transgene-specific CD8(+) T cells into typically exhausted T cells with high programmed cell death 1 (PD-1) expression and lack of IFN-γ production. Our results demonstrate that successful transduction of muscle tissue can be achieved through liver-mediated control of humoral and cytotoxic T cell responses, even in the presence of preexisting immunity to the muscle-associated transgene.